How Do Shopping Enjoyment and Social Media Addiction Influence Impulse Buying Behavior? A Study of FOMO Among TikTok Shop Users - Monata, Deri; Pawirosumorto, Suharno; Lusiana, Lusiana; Sari, Silvia (Jurnal Doktor Manajemen (JDM), 2025)
This research aims to analyze the effect of Shopping Enjoyment and Social Media Addict on Impulse Buying mediated through FoMO in Tiktok Shop users. The subjects in this study were consumers who had shopped at least twice in the Tiktok application. The sample used in this study were 102 respondents. The sample collection technique in this study was non-probability sampling with the method used, namely purposive sampling. By using a quantitative approach. The data collection technique in this study used a questionnaire distribution instrument (questionnaire) . The data analysis used is statistical analysis in the form of SEM-PLS 4.0. The results in this study indicate that (1) Shopping Enjoyment has a positive and significant effect on FoMO, (2) Social Media Addict has a positive and significant effect on FoMO, (3) FoMO has a positive and insignificant effect on Impulse Buying, (4) Shopping Enjoyment has a positive and significant effect on Impulse Buying, (5) Social Media Addict has a positive and insignificant effect on Impulse Buying, (6) Shopping Enjoyment has a positive and insignificant effect on Impulse Buying through FoMO mediation, (7) Social Media Addict has a positive and insignificant effect on Impulse Buying through FoMO mediation.